Fungi from dead arthropods and bats of Gomantong cave, northern Borneo, Sabah (Malaysia) - Ibrahem G. Wasti; Foo, She Fui; Tan Qin Zhi; Cheh, Wai Mun; Mohammad Hafiz Syukri Kassim; Mahadimenakbar Mohd Dawood; Noor Haliza Hasan; Vijay Kumar Subbiah; Faisal Ali Anwarali Khan; Jaya Seelan Sathiya Seelan (NATL SPELEOLOGICAL SOC, 2020)
Borneo is a biodiversity and ecotourism hotspot, yet one of its least-studied ecosystems is their limestone caves. Not many studies have been conducted on the role fungi play in tropical cave ecosystems, and no fungal surveys have been conducted in the caves of Sabah, Malaysia. Here, we assess the mycofloral diversity on bat and arthropod cadavers in one of the most popular ecotourism destinations of northern Borneo, Gomantong caves. Opportunistic sampling of cadavers within the Semud Hitam chamber of Gomantong cave yielded nine dead arthropods and four dead bats. Twenty-four culturable fungi were isolated, of which 14 morphological taxonomic units (MTU) were observed. Twelve of the 14 MTUs underwent molecular characterization of the ITS gene region to confirm identification. All fungi were Ascomycetes except for one Basidiomycete isolate. Aspergillus spp. had the highest occurrence (45.8%), followed by Penicillium spp. (25.0%), and Fusarium sp. (12.5%). Ceratobasidium sp., Diaporthe sp., Pestalotiopsis sp., and Xylaria feejeensis were isolated once each. No more than one fungal taxon was isolated from each arthropod cadaver, and not all arthropods yielded culturable fungi. Bat cadavers yielded 14 out of 24 isolates (58.3%), with the highest occurrence of the fungi sampled from their skin. Our results corroborate that bats and arthropods play a role in fungal dispersion and introduction in the cave because their exteriors are likely to harbor fungi they are exposed to in the environment. We also conclude that cadavers are important substrates for fungal growth and proliferation, perpetuating the role of fungi as important decomposers in caves. This study provides a baseline of information of the mycobiome of Bornean caves for future bioprospecting and potential biotechnological applications.